Hydrogen-bonded organic frameworks (HOFs): a new class of porous crystalline proton-conducting materials - Karmakar, Avishek; Illathvalappil, Rajith; Anothumakkool, Bihag; Sen, Arunabha; Samanta, Partha; Desai, Aamod V.; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2016)
Two porous hydrogen-bonded organic frameworks (HOFs) based on arene sulfonates and guanidinium ions are reported. As a result of the presence of ionic backbones appended with protonic source, the compounds exhibit ultra-high proton conduction values (sigma) 0.75x 10(-2)Scm(-1) and 1.8x10(-2)Scm(-1) under humidified conditions. Also, they have very low activation energy values and the highest proton conductivity at ambient conditions (low humidity and at moderate temperature) among porous crystalline materials, such as metal-organic frameworks (MOFs) and covalent organic frameworks (COFs). These values are not only comparable to the conventionally used proton exchange membranes, such as Nafion used in fuel cell technologies, but is also the highest value reported in organic-based porous architectures. Notably, this report inaugurates the usage of crystalline hydrogen-bonded porous organic frameworks as solid-state proton conducting materials.
Keywords: guanidinium; hydrogen-bonded organic frameworks; porous crystalline frameworks; proton conduction; sulfonates

Hierarchical nanoflower arrays of Co9S8-Ni3S2 on nickel foam: a highly efficient binder-free electrocatalyst for overall water splitting - Illathvalappil, Rajith; Walko, Priyanka S.; Kanheerampockil, Fayis; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Chemistry-A European Journal, 2020)
Hydrogen production is vital for meeting future energy demands and managing environmental sustainability. Electrolysis of water is considered as the suitable method for H-2 generation in a carbon-free pathway. Herein, the synthesis of highly efficient Co9S8-Ni3S2 based hierarchical nanoflower arrays on nickel foam (NF) is explored through the one-pot hydrothermal method (Co9S8-Ni3S2/NF) for overall water splitting applications. The nanoflower arrays are self-supported on the NF without any binder, possessing the required porosity and structural characteristics. The obtained Co9S8-Ni3S2/NF displays high hydrogen evolution reaction (HER), as well as oxygen evolution reaction (OER), activities in 1 m KOH solution. The overpotentials exhibited by this system at 25 mA cm(-2) are nearly 277 and 102 mV for HER and OER, respectively, in 1 m KOH solution. Subsequently, the overall water splitting was performed in 1 m KOH solution by employing Co9S8-Ni3S2/NF as both the anode and cathode, where the system required only 1.49, 1.60, and 1.69 V to deliver the current densities of 10, 25, and 50 mA cm(-2), respectively. Comparison of the activity of Co9S8-Ni3S2/NF with the state-of-the-art Pt/C and RuO2 coated on NF displays an enhanced performance for Co9S8-Ni3S2/NF both in the half-cell as well as in the full cell, emphasizing the significance of the present work. The post analysis of the material after water electrolysis confirms that the surface Co(OH)(2) formed during the course of the reaction serves as the favorable active sites. Overall, the activity modulation achieved in the present case is attributed to the presence of the open-pore morphology of the as formed nanoflowers of Co9S8-Ni3S2 on NF and the simultaneous presence of the surface Co(OH)(2) along with the highly conducting Co9S8-Ni3S2 core, which facilitates the adsorption of the reactants and subsequently its conversion into the gaseous products during water electrolysis.
Keywords: cobalt sulfide; electrocatalysts; Hydrogen evolution; overall water splitting; oxygen evolution

Hydroxide ion-conducting viologen-bakelite organic frameworks for flexible solid-state zinc-air battery applications - Rase, Deepak; Illathvalappil, Rajith; Singh, Himan Dev; Shekhar, Pragalbh; Leo, Liya S.; Chakraborty, Debanjan; Haldar, Sattwick; Shelke, Ankita; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Nanoscale Horizons, 2023)
Adaptable polymer-based solid-state electrolytes can be a game-changer toward safe, lightweight flexible batteries. We present a robust Bakelite-type organic polymer covalently decked with viologen, triazine, and phenolic moieties. Its flexible structure with cationic viologen centers incorporates counter-balancing free hydroxide ions into the polymeric framework. By design, the aromatic groups and heteroatoms in the framework can be activated under an applied potential to prompt a push-pull drive, setting off the towing of hydroxide ions via weak electrostatic, van der Waals, and hydrogen-bond interactions. The frontier orbitals from a DFT-modeled structure certify this. The hydroxyl-polymer requires minimal KOH wetting to maintain a humid environment for Grotthuss-type transport. The hydroxide ion conductivity reaches a value of 1.4 x 10(-2) S cm(-1) at 80 degrees C and 95% RH, which is retained for over 15 h. We enhanced its practical utility by coating it as a thin solid-state separator-cum-electrolyte on readily available filter paper. The composite exhibits a conductivity of 4.5 x 10(-3) S cm(-1) at 80 degrees C and 95% RH. A zinc-air battery (ZAB) constructed using this polymer-coated paper as electrolyte yields a maximum power density of 115 mW cm(-2) and high specific capacitance of 435 mA h g(-1). The power density recorded for our ZAB is among the best reported for polymer electrolyte-based batteries. Subsequently, the flexible battery fabricated with IISERP-POF11_OH@FilterPaper exhibits an OCV of 1.44 V, and three batteries in series power a demo traffic signal. To underscore the efficiency of hydroxide ion transport through the complex multifunctional backbone of the polymer, we calculated the diffusion coefficient for OH- (Exp: 2.9 x 10(-5) cm(2) s(-1); Comp. 5.2 x 10(-6) cm(2) s(-1)) using electrochemical methods and MD simulations. Climbing-edge NEB calculations reveal a large energy barrier of 2.11 eV for Zn2+ to penetrate the polymer and identify hydroxide ions within the polymer, suggesting no undesirable Zn2+ crossover. Our findings assert the readily accessible C-C-linked cationic polymer's capacity as a solid-state electrolyte for ZABs and any anion-conducting membrane.

High-performance sultone-modified PVA/PAMPS semi-IPN hydrogels for proton exchange membranes - Patwadkar, Manjusha V.; Illathvalappil, Rajith; Torris, Arun; Francis, Sifa C.; Kurungot, Sreekumar; Badiger, Manohar V. (Journal of Applied Polymer Science, 2026)
Hydrogel membranes composed of poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) and sultone-modified poly(vinyl alcohol) (PVA) were successfully synthesized and evaluated as promising proton-conducting materials. A key advantage involves the premodification of PVA with 1,3-propane sultone to introduce sulfonic acid groups, thereby imparting proton conductivity to the PVA backbone. This sultone-modified PVA was then physically entangled within a PAMPS cross-linked network to form novel semi-interpenetrating network (semi-IPN) hydrogels. This synergistic design leverages the excellent film-forming and mechanical properties of PVA with the high proton conductivity inherent to PAMPS. The synthesized membranes exhibited robust mechanical properties, with tensile strengths ranging from 5 to 30 MPa and percentage elongations between 200% and 400%, depending on their humidity content. These hydrogel membranes demonstrated proton conductivities ranging from 0.6 to 4.3 x 10-2 S cm-1. The activation energy for proton conduction was found to be as low as 3.5 kJ mol-1, significantly lower than that of the commercial benchmark membrane, Nafion 117 (12 kJ mol-1). These findings underscore the potential of these novel PAMPS/sultone-modified PVA semi-IPN hydrogel membranes for advanced fuel cell applications.
Keywords: batteries and fuel cells; functionalization of polymers; Gels; membranes; polyelectrolytes